Molecular imaging to support cancer immunotherapy. Issue 8 (3rd August 2022) - van de Donk, Pim P; Oosting, Sjoukje F; Knapen, Daan G; van der Wekken, Anthonie J; Brouwers, Adrienne H; Lub-de Hooge, Marjolijn N; de Groot, Derk-Jan A; de Vries, Elisabeth GE
Abstract : The advent of immune checkpoint inhibitors has reinvigorated the field of immuno-oncology. These monoclonal antibody-based therapies allow the immune system to recognize and eliminate malignant cells. This has resulted in improved survival of patients across several tumor types. However, not all patients respond to immunotherapy therefore predictive biomarkers are important. There are only a few Food and Drug Administration-approved biomarkers to select patients for immunotherapy. These biomarkers do not consider the heterogeneity of tumor characteristics across lesions within a patient. New molecular imaging tracers allow for whole-body visualization with positron emission tomography (PET) of tumor and immune cell characteristics, and drug distribution, which might guide treatment decision making. Here, we summarize recent developments in molecular imaging of immune checkpoint molecules, such as PD-L1, PD-1, CTLA-4, and LAG-3. We discuss several molecular imaging approaches of immune cell subsets and briefly summarize the role of FDG-PET for evaluating cancer immunotherapy. The main focus is on developments in clinical molecular imaging studies, next to preclinical studies of interest given their potential translation to the clinic.